2013
DOI: 10.1557/jmr.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of pH and temperature double-sensitive nanocomposite hydrogels consisting of poly(dimethylaminoethyl methacrylate) and clay

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…An absorption peak around 1635 cm −1 was detected due to the bend vibration of CC groups which shows that the considerable CC groups remain in PDMAEMA Hgs‐11 sample. Chen and coworkers reported that the existed CC groups is indicative of the presence of incomplete reacted monomer . Reversely, the intensity of the absorption was low in the spectra of Hgs‐1 and Hgs‐6 samples, indicating the nearly complete reaction of monomer in the hydrogels prepared at low gel preparation concentration.…”
Section: Resultsmentioning
confidence: 99%
“…An absorption peak around 1635 cm −1 was detected due to the bend vibration of CC groups which shows that the considerable CC groups remain in PDMAEMA Hgs‐11 sample. Chen and coworkers reported that the existed CC groups is indicative of the presence of incomplete reacted monomer . Reversely, the intensity of the absorption was low in the spectra of Hgs‐1 and Hgs‐6 samples, indicating the nearly complete reaction of monomer in the hydrogels prepared at low gel preparation concentration.…”
Section: Resultsmentioning
confidence: 99%
“…At low pH values, the protonation keeps polymer chains hydrophilic even when the hydrogen bonding is destroyed at high temperatures. However, at pH values higher than p K a , the deprotonation results in co‐occurrence of both hydrogen bonding and hydrophobic interactions where the latter predominates. In other words, in basic solution, the PDMAEMA chains quickly collapse due to the powerful hydrophobic interactions and less thermal energy is needed for phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…This structure favored the release of the content by electrical stimulation which changed the redox state of the polypyrrole (55). The use of copolymers in the preparation of the composites was recurrent in the studies found (11, 29,52,55,58,60,61). The copolymers associate different polymer units, achieving synergistic effects for certain properties or associating different characteristics.…”
Section: Polymersmentioning
confidence: 99%
“…Therefore, the physically crosslinked hydrogel by Laponite proved suitable for biological applications given its volume phase transition temperature at around 40°C approaching that of the human body, and also due to the ability to reversible stimuliresponsiveness (60). Moreover, other approaches involved double-responsive composites, whose release was modulated by both pH and temperature (29,58,89).…”
Section: Modified Drug Release Systems: Improvements Derived From Orgmentioning
confidence: 99%